Análise quasi-estática e dinâmica de pavimentos asfálticos - Evangelista Junior, Francisco (2006)
This works presents the formulation of an algorithm for the solution of the dynamic equilibrium equation for viscoelastic media. The algorithm is based on the Average Acceleration Method which belongs to the Newmark algorithm family. The formulation was implemented in a code using the Finite Element Method (FEM) and Object Oriented Programming (OOP). Although the formulation used herein is applied to asphalt pavements, it can be used for any type of structure, geometry and boundary conditions due to the flexibility of the FEM and generalization introduced through the OOP. This study shows, mainly, the importance of considering inertial forces (dynamic analyses) in stress and strain analysis of asphalt pavements. The numerical simulations compare the quasi-static and dynamic responses for two types of mixtures (Hot Mix Asphalt and Sand Asphalt); two constitutive models for these materials (elastic and viscoelastic), and various pulse loads. The results give some information about the main parameters used in pavement design: (i) vertical displacements at the top of surface (asphalt) layer (dv); (ii) tensile stress at the bottom of the surface layer (σxx), and (iii) compression stress (σyy) at the top of subgrade. Factorial analyses showed that, for current pavement design procedures which assume an elastic surface layer, static loads without inertial forces, may lead to non-conservative predictions. As an example, the results of the tensile stress at the top of the surface layer (σxx), show that the interaction of the asphalt layer viscoelastic behavior with other factors may conduct to significantly relative differences in that stress predictions. Thus, the structural assumptions needs to be more discussed for design purposes, since longer pulse loads (lower vehicle speeds) increase dv, while shorter pulse loads (higher vehicles speeds) increase σxx. Analyses considering the temporally passage of multiple wheels, for the gears of some vehicle configurations, showed no temporal superposition of the effects of multiple loads (pulses longer than 0.008s) in the structural responses considered herein even considering viscoelastic and/or dynamic analyses. Alternative methodologies for the curve fitting and interconversition of viscoelastic functions are also presented. The proposed algorithms use optimization concepts to minimize the errors in the calculation of the required function.